On the polar edge: the status of the northern gannet (Morus bassanus) in the Barents Sea in 2015-16. Issue 1 (1st January 2017) - Barrett, Robert T.; Strøm, Hallvard; Melnikov, Mikhail
ABSTRACT: During its population recovery in the North Atlantic in the early 1900s, the northern gannet ( Morus bassanus ) established its first colony in Norway at Runde in 1946. Since the 1960s, gannets have established (and later abandoned) several small colonies in the north of the country. These colonies have been regularly monitored, and in 2015–16 ca. 3300 apparently occupied nests (AON) were counted in seven colonies in northern Norway. Two colonies that existed in 2008 had been abandoned and four new ones established. Two of the latter were again abandoned before 2015. In 1995, one pair established a colony at Kharlov on the Kola Peninsula, Russia, where numbers increased to 200–250 AON in 2016. The newest and world's northernmost colony was established at Bjørnøya (Bear Island) in 2011, extending the species' breeding range well into the Arctic. These recent establishments are thought to be associated with a warming of the Barents Sea and the northward spread of common prey of the gannet such as herring and mackerel. This paper documents recent establishments, growths and abandonments of colonies at the gannet's northern limit of distribution.